The role of mechanical stretch and TGF-β2 in epithelial-mesenchymal transition of retinal pigment epithelial cells - Cao, Qian (Int J Ophthalmol, 2019)
AIM: To explore the effects and mechanisms of mechanical stress and transforming growth factor-beta2 (TGF-β2) on epithelial-mesenchymal transition (EMT) in cultured human retinal pigment epithelial (RPE) cells. METHODS: Human RPE cells were inoculated on BioFex 6-well plates and RPE cells received 0, 1, 2, 3, or 4 mild stretch injuries delivered 3h apart after 24h of culture. The device of mechanical stress parameters were set to sine wave, frequency 1 Hz, stretch strength 20%. For treatment with TGF-β2, when the inoculated RPE cells in 6-well plates were around 60% conﬂuent, serum was reduced to 0 for 12h and recombinant human TGF-β2 (0, 1, 5, 10 ng/mL) was added for 48h. α-SMA, Vimentin and N-Cadherin, fibronectin proteins expressions were detected by Western blotting, confocal cell immunofluorescence and quantitative real-time polymerase chain reaction (qRT-PCR). Then we detected the change of miRNA-29b and ascertained the changes of phosphatidylinositol 3-kinase-serine threonine protein kinase (PI3K/Akt) pathway after RPE cells were stretched by the device of mechanical stress and induced by TGF-β2 by Western blotting, confocal cell immunofluorescence and qRT-PCR. RESULTS: Mechanical stress induce EMT and activate the PI3K/Akt pathway in ways that lead to the EMT process. TGF-β2 induce RPE cells EMT and in a certain range and TGF-β2 decrease the miRNA-29b expression in RPE cells, and the inhibitory effect is more obvious with the increase of TGF-β2 concentration. CONCLUSION: Our findings are crucial steps in determining the critical roles of the PI3K/Akt signaling pathway and miRNA-29b in pathogenesis of proliferative vitreoretinopathy (PVR) which may be a potential target for preventing or treating PVR.